Drying process of clay ceramic materials: a review (Research, Society and Development, 2020)
Drying is a heat and mass transfer operation involving the removal of moisture, being an important and expensive step in the manufacturing process of several products. For ceramic materials, the drying process is necessary to remove the water that was added to the clay in the molding step and to provide the necessary strength to reduce the chances of failure during the product firing step. Control of the drying process is essential to reduce defects in the material, loss of productivity and energy consumption. Due to its importance, this work aims to present a review of several topics related to the drying of ceramic materials. Here, different aspects are discussed, such as: the fundamentals, moisture removal kinetics, defects, control and optimization of the drying process, with emphasis on clay products. The idea is to provide subsidies so that researchers and industrialists can improve their knowledge and make appropriate decisions on this topic of great importance for the country's economy.